P175 A national small business intervention: lockout and tagout. (1st September 2016) - Parker, David; Yamin, Samuel
Abstract : Objective: In 1989, the Occupational Safety and Health Administration (OSHA) promulgated standard 1910.147 to regulate practices for the control of hazardous energy. The OSHA standard covers servicing and maintaining machines and equipment in which the unexpected release of energy or inadvertent start-up could injure employees. Hazard controls for these tasks are collectively known as lockout/tagout (LOTO). Failure to implement lockout/tagout (LOTO) procedures adversely affects the rate of work-related fatalities and serious traumatic injury and is one of the most frequently cited OSHA standards. Methods: Insurance safety consultants conducted a standardised and validated evaluation of LOTO programs and procedures. Businesses received a baseline evaluation, two intervention visits and a 12-month follow-up evaluation. Results: The intervention was completed by 160 out of 221 businesses. At bseline, businesses with a safety committee had better baseline LOTO procedures and LOTO programs when compared with those without one.The mean LOTO procedure score improved from 8% to 33% (p < 0.0001), the mean program score went from 55% to 76% (p < 0.0001), and the presence of lockable disconnects went from 88% to 92% (p < 0.0001). Conclusions: By the end of the study, substantial and statistically significant improvements had been made in the proportion of shops that had posted of LOTO procedures, verification of employee training, designation of one or more authorised employees, and presence of LOTO programs, all of which are fundamental aspects of LOTO practice.This nationwide intervention showed substantial improvements in LOTO. It provides a framework for assessing and improving LOTO.